An energy efficient dynamic small cell on/off switching with enhanced k-means clustering algorithm for 5G HetNets. (3rd January 2023) - Natarajan, Janani; Rebekka, B.
The massive growth in the current and envisaged cellular traffic lead to innovations in 5G heterogeneous networks (HetNets) and implementation technologies. The small cells (SCs) or small base stations (SBS) aided macro base station (MBS) topology in HetNets effectively accomplish capacity growth and spectrum reuse at the cost of network complexity, power consumption and energy efficiency. In this paper, we propose a mechanism to maximise the system energy efficiency jointly by enhanced k-means clustering and dynamic load based SC switching algorithm for HetNets. The clustering algorithm optimises the initial centroids for maximum inter-cluster separation. Within each cluster, SC switching is decided based on a permissible threshold of inter-cluster interference. Further, the intra cluster SC coordination is formulated as a cooperative game for load balancing. Simulation results illustrate performance improvement of the proposed scheme up to 20% in energy efficiency and 16% in system throughput compared to conventional k-means clustering approach.